2017
DOI: 10.1007/s00394-017-1469-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing fruit and vegetable intake by dietary intervention on nutritional biomarkers and attitudes to dietary change: a randomised trial

Abstract: PurposeLow fruit and vegetable consumption is linked with an increased risk of death from vascular disease and cancer. The benefit of eating fruits and vegetables is attributed in part to antioxidants, vitamins and phytochemicals. Whether increasing intake impacts on markers of disease remains to be established. This study investigates whether increasing daily intake of fruits, vegetables and juices from low (approx. 3 portions), to high intakes (approx. 8 portions) impacts on nutritional and clinical biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 57 publications
6
62
1
1
Order By: Relevance
“…On the contrary, those who had low incomes and received medical aid were less likely to have an appropriate diet quality (Mogre et al, 2019). This is consistent with a previous study which reported that many patients perceived healthy foods as being more expensive, and that these high costs function as barriers that prevent the adoption of a healthy diet and the selection of healthy foods (Cho and Park, 2018;Duthie et al, 2018;Koutoukidis et al, 2017).…”
Section: Tablesupporting
confidence: 88%
“…On the contrary, those who had low incomes and received medical aid were less likely to have an appropriate diet quality (Mogre et al, 2019). This is consistent with a previous study which reported that many patients perceived healthy foods as being more expensive, and that these high costs function as barriers that prevent the adoption of a healthy diet and the selection of healthy foods (Cho and Park, 2018;Duthie et al, 2018;Koutoukidis et al, 2017).…”
Section: Tablesupporting
confidence: 88%
“…White meat and dairy products are beneficial foods which contribute to the prevention of T2DM [ 19 , 20 ]. Increased consumption of fruits and vegetables is associated with a reduced risk of T2DM not only because they contain dietary fibre, essential vitamins and minerals, but also due to the antioxidant and anti-inflammatory effects of their components which include vitamins B and C, carotenoids, and polyphenols [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential oxidation resistance of vitamin C, researchers attributed this association to that vitamin C could prevent the formation of free radicals, thereby reducing the vascular oxidative in the progress of hypertension [27]. However, these preliminary findings have not been confirmed, since some researchers drew an opposite conclusion, like the study conducted by Duthie et al [28]. Even relevant systematical review and meta-analysis articles have not been found regarding the relationship between them.…”
Section: Introductionmentioning
confidence: 97%